Human surface anatomy terminology for dermatology: a Delphi consensus from the International Skin Imaging Collaboration. (2nd September 2020) - Navarrete‐Dechent, C.; Liopyris, K.; Molenda, M.A.; Braun, R.; Curiel‐Lewandrowski, C.; Dusza, S.W.; Guitera, P.; Hofmann‐Wellenhof, R.; Kittler, H.; Lallas, A.; Malvehy, J.; Marchetti, M.A.; et al.
Abstract: Background: There is no internationally vetted set of anatomic terms to describe human surface anatomy. Objective: To establish expert consensus on a standardized set of terms that describe clinically relevant human surface anatomy. Methods: We conducted a Delphi consensus on surface anatomy terminology between July 2017 and July 2019. The initial survey included 385 anatomic terms, organized in seven levels of hierarchy. If agreement exceeded the 75% established threshold, the term was considered 'accepted' and included in the final list. Terms added by the participants were passed on to the next round of consensus. Terms with <75% agreement were included in subsequent surveys along with alternative terms proposed by participants until agreement was reached on all terms. Results: The Delphi included 21 participants. We found consensus (≥75% agreement) on 361/385 (93.8%) terms and eliminated one term in the first round. Of 49 new terms suggested by participants, 45 were added via consensus. To adjust for a recently published International Classification of Diseases‐Surface Topography list of terms, a third survey including 111 discrepant terms was sent to participants. Finally, a total of 513 terms reached agreement via the Delphi method. Conclusions: We have established a set of 513 clinically relevant terms for denoting human surface anatomy, towards the use of standardized terminology in dermatologic documentation. Abstract : Linked Commentary : R.J.G. Chalmers. J Eur Acad Dermatol Venereol 2020; 34 : 2456–2457. https://doi.org/10.1111/jdv.16978 .